The CancerGrid Experience: Metadata−Based Model−Driven Engineering for Clinical Trials - Davies, J; Gibbons, J; Harris, S; Crichton, C (2014)
The CancerGrid approach to software support for clinical trials is based on two principles: careful curation of semantic metadata about clinical observations, to enable subsequent data integration, and model-driven generation of trial-specific software artifacts from a trial protocol, to streamline the software development process. This paper explains the approach, presents four varied case studies, and discusses the lessons learned.